Significant reduction in Hepatitis B virus infections following 32 years of universal Hepatitis B vaccination as part of EPI, Thailand - Pornjarim Nilyanimit; Nasamon Wanlapakorn; Preeyaporn Vichaiwattana; Lakkhana Wongsrisang; Sirapa Klinfueng; Nungruthai Suntronwong; Wichan Bhunyakitikorn; Piyada Angsuwatcharakon; Chaninan Sonthichai; Narong Thawinwisan; Pichet Puedkuntod; Sunsanee Phattharasrivongchai; et al. (Scientific Reports)
Abstract This study aimed to evaluate the impact of Thailand’s hepatitis B virus (HBV) National Program Immunization (NPI), 32 years post-implementation, on infection rates and immunity in various age groups. A cross-sectional study involved 6,068 participants aged 6 months to 80 years from four regions in Thailand. Blood samples were tested for HBsAg, anti-HBs, and anti-HBc using a chemiluminescent immunoassay. Data were compared across age groups and with previous surveys from 2004 to 2014. Individuals born after the implementation of the NPI had significantly lower HBV infection rates (p < 0.0001). No HBsAg was detected in individuals under 20 years old. The prevalence of HBV carriers increased with age, from 0.3% in the 21–30 group to 4.3% in those over 60, with an overall prevalence of 1.7%. Percentages of seroprotected individuals (anti-HBs ≥ 10 mIU/mL) were high in young children but dropped to 19.4% in ages 11–20 and 12.5% in ages 21–30. Anti-HBc was found at very low rates in children but increased significantly after age 30. Thailand’s HBV NPI significantly reduced HBV infection rates, especially in younger populations. This study highlighted the program’s success and guided future elimination efforts to achieve hepatitis elimination goal by 2030.